Co-Occurrence of Familial Non-Medullary Thyroid Cancer (FNMTC) and Hereditary Non-Polyposis Colorectal Cancer (HNPCC) Associated Tumors—A Cohort Study - Aswath, Kshama; Welch, James; Gubbi, Sriram; Veeraraghavan, Padmasree; Avadhanula, Shirisha; Gara, Sudheer Kumar; Dikoglu, Esra; Merino, Maria; Raffeld, Mark; Xi, Liqiang; Kebebew, Electron; Klubo-Gwiezdzinska, Joanna (Frontiers in Endocrinology, 2021)
Familial non-medullary thyroid cancer (FNMTC) is a form of endocrine malignancy exhibiting an autosomal dominant mode of inheritance with largely unknown germline molecular mechanism. Hereditary nonpolyposis colorectal cancer syndrome (HNPCC) is another hereditary autosomal dominant cancer syndrome which, if proven to be caused by germline mutations in mismatch repair genes (MMR)—MLHL, MSH2, MSH6, PMS2, and EPCAM—is called Lynch syndrome (LS). LS results in hereditary predisposition to a number of cancers, especially colorectal and endometrial cancers. Tumors in LS are characterized by microsatellite instability (MSI) and/or loss of MMR protein expression in immunohistochemistry (IHC). MSI is a rare event in thyroid cancer (TC), although it is known to occur in up to 2.5% of sporadic follicular TC cases. There are limited data on the role of germline MMR variants FNMTC. The goal of this study was to analyze the potential clinical and molecular association between HNPCC and FNMTC. We performed a cohort study analyzing the demographic, clinical, and pathologic data of 43 kindreds encompassing 383 participants (104 affected, 279 unaffected), aged 43.5 [7-99] years with FNMTC, and performed high-throughput whole-exome sequencing (WES) of peripheral blood DNA samples of selected 168 participants (54 affected by FNMTC and 114 unaffected). Total affected by thyroid cancer members per family ranged between 2 and 9 patients. FNMTC was more prevalent in women (68.3%) and characterized by a median tumor size of 1.0 [0.2-5.0] cm, multifocal growth in 44%, and gross extrathyroidal extension in 11.3%. Central neck lymph node metastases were found in 40.3% of patients at presentation, 12.9% presented with lateral neck lymph node metastases, and none had distant metastases. Family history screening revealed one Caucasian family meeting the clinical criteria for FNMTC and HNPCC, with five members affected by FNMTC and at least eight individuals reportedly unaffected by HNPCC-associated tumors. In addition, two family members were affected by melanoma. Genome Analysis Tool Kit (GATK) pipeline was used in variant analysis. Among 168 sequenced participants, a heterozygous missense variant in the MSH2 gene (rs373226409; c.2120G>A; p.Cys707Tyr) was detected exclusively in FNMTC- HNPCC- kindred. In this family, the sequencing was performed in one member affected by FNMTC, HPNCC-associated tumors and melanoma, one member affected solely by HNPCC-associated tumor, and one member with FNMTC only, as well as seven unaffected family members. The variant was present in all three affected adults, and in two unaffected children of the affected member, under the age of 18 years, and was absent in non-affected adults. This variant is predicted to be damaging/pathogenic in 17/20 in-silico models. However, immunostaining performed on the thyroid tumor tissue of two affected by FNMTC family members revealed intact nuclear expression of MSH2, and microsatellite stable status in both tumors that were tested. Although the MSH2 p.Cys707Tyr variant is rare with a minor allele frequency (MAF) of 0.00006 in Caucasians; it is more common in the South Asian population at 0.003 MAF. Therefore, the MSH2 variant observed in this family is unlikely to be an etiologic factor of thyroid cancer and a common genetic association between FNMTC and HNPCC has not yet been identified. This is the first report known to us on the co-occurrence of FNMTC and HNPCC. The co-occurrence of FNMTC and HNPCC-associated tumors is a rare event and although presented in a single family in our large FNMTC cohort, a common genetic background between the two comorbidities could not be established.